Effects of microplastics on soil physicochemical properties and vertical migration and transformation of chromium - Jia-li Li; Na-ying Li; Jia Ni; Rui-lin Wan; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Hierarchical conducting networks constructed as resistive strain sensors for personal healthcare monitoring and robotic arm control - Huijuan Lin; Jia Wang; Wei Cao; Huinan Wang; Kun Rui; Yan Yan; Jixin Zhu (Chemical Engineering Journal, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)